A Survey of Pregnancies Complicated by Antepartum Haemorrhage (Medical Forum Monthly, 2024)
Objective: To find out the demographic profile, type of antepartum haemorrhage, maternal and perinatal complications and maternal and perinatal mortality.Study Design: Prospective studyPlace and Duration of Study: This study was a carried out at Gynae B, Labour Room, Khyber Teaching Hospital Peshawar for a period of one year from January 2013 to December 2013.Materials and Methods: This study was carried over on patients who presented to gynae B labour room Khyber Teaching Hospital Peshawar with antepartum haemorrhage. All the patients were admitted and relevant informations including age, parity, booking status, education, residence and occupation etc. were noted in the study proforma. Patients were followed till discharge.Records about mode of delivery, intrapartum and postpartum complications were made. Details of the babies like weght, sex, maturity, apgar score, whether live or dead were recorded and data analyzed.Result: Incidence of ante partum haemorrhage was 3.01% Maternal and perinatal morbidity was very high with increase rates of anaemia (100%) cesarian section rates (68%) post partum haemorrhage (11.5%), need of blood transfusion (100%). Puerperal pyrexia (13.1%) coagulation failure (11.5%) low birth weight (36%) and birth asphyxia. Maternal and perinatal mortality was very high( 2.1%) and (37%) respectively.Conclusion: Antepartum haemorrhage is a grave obstetrical emergency associated with very high maternal and perinatal mortality and morbidity.